Efficacy of topical insulin versus normal saline in promoting granulation tissue formation and healing in diabetic foot ulcers: a prospective non-randomized interventional comparative study - Baid, Saloni; Sharma, Raj Kumar; Sharma, Mukul; Sharma, Sachin (International Surgery Journal, 2025)
Background: Diabetic foot ulcers (DFUs) represent a severe complication of diabetes mellitus, substantially increasing the risk of morbidity, extended hospital stays and potential limb amputation. Conventional management strategies often yield suboptimal healing outcomes, necessitating exploration of novel therapies. Topical insulin has emerged as a potential adjunct due to its mitogenic, angiogenic and anti-inflammatory properties. To evaluate the efficacy of topical insulin versus normal saline in promoting granulation tissue formation and wound healing in patients with diabetic foot ulcers. Methods: A prospective, non-randomized interventional comparative study was conducted at Dr. R.P.G.M.C. Kangra at Tanda over one year, enrolling 40 patients with Wagner grade I–II DFUs. Patients were allocated into two groups: Group A (Topical Insulin) received dressings with 30 IU regular human insulin in 30 ml normal saline, while Group B (Control) received normal saline dressings alone. Granulation tissue percentage, ulcer area and fasting blood sugar (FBS) levels were assessed at baseline, 1 week and 3 weeks. Results: Significant improvements in fasting blood sugar (FBS) levels and ulcer area were observed within both groups. However, Group A exhibited a significantly greater increase in granulation tissue formation (from 21.44% to 73.74%) compared to Group B (from 17.46% to 56.6%) at 3 weeks (p<0.05). No significant inter-group difference was observed in ulcer area reduction within the study duration. Conclusions: Topical insulin significantly enhances granulation tissue formation in DFUs and represents a safe, cost-effective adjunct to conventional therapy, particularly beneficial in resource-limited settings.